IMPLEMENTASI MAQASHID SYARIAH PADA PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DI BANK UMUM SYARIAH BANDA ACEH - Novia, Diva; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine whether there are implementation Maqashid Syariah of CSR programs at Syariah Bank in Banda Aceh. The results of weighting the CSR program also determine the Banda Aceh sharia bank that implements Maqashid Syariah the best. The research method used in the research is descriptive analysis research. The type of data used is primary data obtained through interviews with parties directly related to the provision of CSR programs at each bank, this data is also supported by secondary data in the form of a list of CSR activities that have been carried out. The results of this study indicate that there is a true implementation of Maqashid Syariah in implementing CSR in every Islamic bank in Banda Aceh. The data also shows that the best Islamic banks in implementing Maqashid Syariah have the highest score of 25, where the score shows that the implementation is categorized as "very good" over the highest score weights obtained.